SOCIOLOGICAL REVIEW OF ISLAMIC EDUCATION CURRICULUM: THE IMPACT OF SOCIAL CHANGE AND ECONOMIC MOBILITY ON CURRICULUM RELEVANCE - Nur Aziza Turrohmah; Moh Sabiq Al Hadi (As-Sulthan Journal of Education, 2025)
This study aims to analyze the impact of social change and economic mobility on the relevance of the Islamic education curriculum at MAN 3 East Seram through a sociological approach. Changes in the structure of society due to globalization, technological transformation, and the shift of the economy from the agricultural sector to the service sector have given rise to new demands for a more adaptive and applicable curriculum. This study uses a qualitative method with a case study approach, combining in-depth interviews, participatory observation, and documentation studies. The findings show that the community expects the curriculum to not only teach religious knowledge, but also equip students with vocational skills, digital literacy, and entrepreneurship. However, this transformation process faces challenges in the form of cultural resistance, limited infrastructure, and minimal teacher training. This study also found that teachers have an important role as agents of change who bridge Islamic values with the demands of the times through contextual learning innovations. In addition, increasing economic mobility in the region has an impact on expanding access to education, but also creates new social stratification in utilizing opportunities. These findings strengthen the theory of the sociology of education on curriculum adaptation to external pressures and offer a curriculum development model based on local participation and social sensitivity. This research is expected to provide practical contributions for policy makers in designing Islamic education curricula that are relevant, contextual, and competitive amidst the dynamics of modern society.